Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1037/lat0000141
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial effects of discrimination, legal status fears, adverse childhood experiences, and harsh working conditions among Latino migrant farmworkers: Testing learned helplessness hypotheses.

Abstract: Migrant farmwork is often characterized by harsh working conditions that carry significant physical and mental health consequences. Using a learned helplessness framework, the current study examined the extent to which discrimination, immigration legal status difficulties, and adverse childhood experiences moderated the effects of harsh working conditions on depression and anxiety. The study also examined the extent to which harsh working conditions mediated the effects of discrimination, immigration legal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…Each item was measured on a Likert-type scale from 1 not at all stressful to 4 extremely stressful. Prior work with this sample had suggested that a single factor approach did not adequate fit the data and that a five-item, theoretically driven factor containing only items that specifically reference work conditions provided adequate fit (Andrews et al, 2019).…”
Section: Migrant Farmworker Stressmentioning
confidence: 95%
“…Each item was measured on a Likert-type scale from 1 not at all stressful to 4 extremely stressful. Prior work with this sample had suggested that a single factor approach did not adequate fit the data and that a five-item, theoretically driven factor containing only items that specifically reference work conditions provided adequate fit (Andrews et al, 2019).…”
Section: Migrant Farmworker Stressmentioning
confidence: 95%
“…This paper synthesizes the research on how participation in early care and education programs might serve as a critical protective factor for Latino children’s development and mitigate their exposure to adverse childhood experiences (ACEs). Latino populations have been shown to have some of the highest rates of exposure to ACEs (Andrews, Haws, Acosta, Acosta Canchila, Carlo, et al, 2019 ; Ellis & Dietz, 2017 ; Slopen, Shonkoff, Albert, Yoshikawa, Jacobs, Stoltz, et al, 2016 ). To guide the synthesis, a theoretical perspective is described which incorporates the sociocultural and transactional context that must be considered in examining ACEs among Latino children, their families, and ECE programs or providers.…”
Section: Overview Of the Papermentioning
confidence: 99%
“…Job stress and low rates of health insurance among Latinos are found using national data, with only half of US-born Latino fathers and 35% of foreign-born Latino fathers having jobs offering employer-sponsored health insurance (Wildsmith, Ramos-Olazagasti, Alvira-Hammond, 2018 ). In a study of Latino migrant farmworkers, ACEs were related to higher exposure to harsh working conditions, and to larger effects of these harsh working conditions on depression and anxiety symptoms (Andrews et al, 2019 ). Taken together, all these factors create stress and uncertainty, which is a risk to the stability of the family unit and parent’s mental health, which can compromise parents’ ability to buffer their own children from ACEs.…”
Section: Overview Of Adversity and Resilience In Latino Childrenmentioning
confidence: 99%
See 2 more Smart Citations